An Ecology of Operations: Vigilance, Radar, and the Birth of the Computer Screen. - GEOGHEGAN, BERNARD DIONYSIUS (Representations)
This article examines the birth of interactive computer screens from enemy targeting and tracking systems (especially computerized radar) that distributed information processing in an ecology of operations among humans, computational instruments, and the environment. It proposes a concept of ''computational screening'' to account for the integration of visualization and information processing that gave rise to digital images.